Clinical Diagnostic Value of Quantitative Hepatitis B Virus Core Antibody Test in Chronic Viral Hepatitis B - Xi Su; Huangping Chen; Zifei Zhu; Wanying Xie; Jianqiao Peng; Xinping Ma; Wenwen Jin; Wei Shi; Zhonghua Deng; Cunyan Li (Bioinorganic Chemistry and Applications)
The level of CHB virus (HBV) core antibody (HBcAb) is different in four stages of chronic HBV infection and may be used for differential diagnosis of the natural history of chronic HBV infection. To address this question, we examined multiple blood biomarkers and assessed the efficacy to diagnose different stages of chronic HBV infection. The quantitative detection of HBcAb, hepatitis B surface antigen (HBsAg), HBV DNA, alanine aminotransferase (ALT), aspartate aminotransferase (AST), and platelet count (PLT) were determined in the serum of 73 cases of low-replicative phase (LR), 46 cases of immune-tolerant phase (IT), 44 cases of immune clearance phase (IC), and 57 cases of HBeAg-negative hepatitis (ENH). Differentiating performance of these serum protein levels was analyzed by receiver operating characteristic (ROC) curve analysis. Our results showed that the levels of HBcAb, ALT, and AST levels were significantly higher in IC and ENH than those in LR and IT (both P≤0.001). The levels of HBV DNA and HBsAg were higher in IC and IT than those in LR and ENH (both P≤0.001). Logistic regression models showed that HBcAb, HBsAg, HBV DNA, ALT, and AST were the independent variables, respectively, and when combined, they provided high diagnostic accuracy for the staging of CHB. To sum up, HBcAb quantification is a new index, which can reflect whether the liver is in the immune activation state of HBV infection, and is related to the inflammatory state of the host liver. The combined detection of HBcAb quantification and other indicators has showed promising efficiency for staging of IC and ENH and can assist the diagnosis and treatment of CHB.